Disaster research and the second environmental crisis assessing the challenges ahead - Kendra, James M. 1965-; Knowles, Scott G.; Wachtendorf, Tricia 1972- (Environmental hazards, 2019)
The 50th anniversary of the Disaster Research Center of the University of Delaware provoked a discussion of the field’s background, its accomplishments, and its future directions. Participants representing many disciplines brought new methods to bear on perennial problems relevant to effective disaster management and policy formation. However, new concerns were raised, stemming from the fact that we live today in a globally unfolding environmental crisis every bit as pressing and worrisome as that of the 1960s when the Disaster Research center was founded. This volume brings together ideas of participants from that workshop as well as other contributors. Topics include: the history and evolution of disaster research, innovations in disaster management, disaster policy, and ethical considerations of disaster research. Readers interested in science and technology, public policy, community action, and the evolution of the social sciences will find much of interest in this collection.